Predicting Low Toxicity and Scalable Solvent Systems for High‐Speed Roll‐to‐Roll Perovskite Manufacturing. Issue 3 (8th March 2022) - Swartwout, Richard; Patidar, Rahul; Belliveau, Emma; Dou, Benjia; Beynon, David; Greenwood, Peter; Moody, Nicole; deQuilettes, Dane; Bawendi, Moungi; Watson, Trystan; Bulovic, Vladimir
Abstract : Safer Ink Systems In article number 2100567, Richard Swartwout and co‐workers demonstrated the coating performance of their new, safer solvent ink mixture with an effective permissible exposure limit 10x higher than traditional DMF/DMSO ink systems. Regulatory requirements limit exposure to solvent vapors generated from ink‐based coating processes. For perovskite photovoltaics, this requires new ink formulations that exclude traditionally hazardous solvents while simultaneously coating uniformly at scale.